The ugly duckling(urdu/ english) - Azeem, Ahmad (Khizer readers Lahore, 2014)
In this classic tale, a duckling is rejected for being different from his siblings, leading him on a journey of self-discovery. As he grows, he transforms into a beautiful swan, teaching the lesson that true beauty lies within and that everyone has their own unique worth.